Call admission control strategy for dynamically setting the number of guard channels in wireless multimedia networks - Mohamed, Nagla Osman; Deniz, Derviş Z. (My University, 2008)
A CAC strategy for dynamically changing the number of guard channels in wireless multimedia networks is proposed. In the proposed strategy, the number of guard channels is not set before hand. The algorithm starts by setting zero number of guard channels and then depending on the measurement of certain parameters, the number of guard channels is either increased, decreased or left as it is without any change. These measurements are performed at periodic time intervals. These time intervals are pre-set by the user. The proposed technique is compared with the traditional guard channel CAC strategy and the results indicate that there is substantial improvement. In the proposed strategy the blocking probability of originating calls is decreased, handoff call dropping is less than for traditional guard channels CAC and bandwidth utilization is increased. © 2008 by Bo?aziçi University.
8th International Symposium on Computer Networks, ISCN'08 --
Keywords: Blocking probability; Cellular radio systems; Computer networks; Computers; Internet; Wireless telecommunication systems; Band-width utilizations; Call admission controls; Guard channels; Handoff calls; Substantial improvements; Time intervals; Wireless multimedia networks; Wireless networks